Exploitation of Beehive Products, Plant Exudates and Tars in Corsica During the Early Iron Age. (19th May 2015) - Rageot, M.; Pêche‐Quilichini, K.; Py, V.; Filippi, J.‐J.; Fernandez, X.; Regert, M.
Abstract : In the north‐western Mediterranean area, the first Iron Age is characterized by intense contacts and cultural interactions between populations. Archaeological remains such as ceramic vessels or metal and glass objects are usually good indicators of the nature and the intensity of these exchanges, but can also be used to determine the way in which these populations were living at their time. In contrast, organic substances, despite their importance in a wide variety of activities, are rarely investigated due to their low degree of preservation. The recent discovery of a series of amorphous organic residues with adhesive properties at the site of Cuciurpula provided a unique opportunity to address questions related to the types of natural substances exploited, their provenance, their uses and their informational input to intercultural relationships. Our results, based on GC and GC–MS analysis of organic residues preserved at the site of Cuciurpula, provide strong evidence for the most southern use of birch bark tar in Western Europe, and also for the simultaneous use of this substance with pine resin. Beeswax was also identified in some samples. The combined study of residue composition, aspect and location on ceramic sherds reveals a variety of uses, highlighting a complex technical system.